Selected properties of oil palm kernel - Asr, Mina Habibi; Ibrahim, Mohd Nordin; Mokhtar, Mohd Noriznan; Md. Yunos, Khairul Faezah; Ibrahim, Nuzul Amri (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Selected physical properties of oil palm kernel are required for its drying studies. The effect of moisture content on physical properties of oil palm kernel was determined in the moisture range of 28-2% (d.b). These include physical dimension, shape, surface area, specific surface area, bulk density and true bulk density. Length, width, thickness of the palm kernel ranged from 16-14 mm, 12-11 mm, 10-9 mm respectively and these dimensions did not vary over the various moisture contents. However, the bulk density, surface area and specific surface area of palm kernel increased linearly as the moisture content increased. There was reduction in porosity and true density as the moisture content increased. A study on equilibrium moisture content of local variety of palm kernel was conducted. At temperature of 50˚C and relative humidity of 50 %, EMC value obtained from other studies was found to be 1 to 3 times higher compared to current study. EMC is found to decrease with increasing temperature and, at constant temperature, EMC increased with increasing relative humidity, which is consistent generally with established EMC behavior. The experimental drying data on single kernel available in the literature was utilized to develop thin layer drying model by fitting the data with several common thin layer drying equations available in the literature. It was found that Lewis model could be fairly used (R2=0.86) to represent thin layer drying of oil palm kernel; however, further study is needed to obtain more suitable thin layer drying model for palm kernel.